Creative Class Mobility and Quality of Life: Migration of Creative Class from Istanbul to Izmir - Shah, Khurshid Ahmad; Gokcen, Sebnem (Faculty of Geography, Universitas Gadjah Mada, 2024)
The place attractiveness determines the movement of creative people in a city. Young and skilled people migrate to Izmir from istanbul because Izmir offers higher standards of life with respect to social indicators and tolerance for people who are different than others. It was observed from the migrated creative people that Izmir has the social and cultural advantage over istanbul to attract these free-thinking talented people. In the case comparative study, it was evident that Izmir has the potential to be creative milieu to develop into creative smart city in the region but Istanbul has some negative externalities such as over population, inaccessibility, conservatism, expensive city. This paper examines the migration of creative professionals from Istanbul to Izmir, testing Florida’s creative class concept and the 3T model (Talent, Technology, Tolerance) via QoL parameters regarding creative migration. A mixed-method approach was used to gather and analyse both quantitative and qualitative data for locational preferences of the creative class. The study finds that young, innovative individuals are attracted to cities with high tolerance, advanced technology, and favourable work conditions. These factors not only enhance their quality of life but also drive economic growth and job creation in Izmir, highlighting that while quality of life attracts talent, career opportunities are crucial for their retention.